Parkinson's disease and long-term exposure to outdoor air pollution: A matched case-control study in the Netherlands. (August 2019) - Toro, Rosario; Downward, George S.; van der Mark, Marianne; Brouwer, Maartje; Huss, Anke; Peters, Susan; Hoek, Gerard; Nijssen, Peter; Mulleners, Wim M.; Sas, Antonetta; van Laar, Teus; Kromhout, Hans; et al.
Abstract: Background: There is some evidence to suggest an association between ambient air pollution and development of Parkinson's disease (PD). However, the small number of studies published to date has reported inconsistent findings. Objectives: To assess the association between long-term exposure to ambient air pollution constituents and the development of PD. Methods: Air pollution exposures (particulate matter with aerodynamic diameter <10 μm [PM10 ], <2.5 μm [PM2.5 ], between 2.5 μm and 10 μm [PMcoarse ], black carbon, and nitrogen oxides [NO2 and NOx ]) were predicted based on land-use regression models developed within the "European Study for Air Pollution Effects" (ESCAPE) study, for a Dutch PD case-control study. A total of 1290 subjects (436 cases and 854 controls). were included and 16 years of exposure were estimated (average participant starting age: 53). Exposures were categorized and conditional logistic regression models were applied to evaluate the association between ambient air pollution and PD. Results: Overall, no significant, positive relationship between ambient air pollutants and PD was observed. The odds ratio (OR) for PD associated with an increase from the first quartile of NO2 (<22.8 μg/m 3 ) and the fourth (>30.4 μg/m 3 ) was 0.87 (95% CI: 0.54, 1.41). For PM2.5 where the contrast in exposure was more limited, the OR associated with an increase from the first quartile PM2.5 (<21.2 μg/m3) to the fourth (>22.3 μg/m3) was 0.50 (95% CI: 0.24, 1.01). In a subset of the population with long-term residential stability ( n  = 632), an increased risk of PD was observed (e.g. OR for Q4 vs Q1 NO2 :1.37, 95% CI: 0.71, 2.67). Conclusions: We found no clear association between 16 years of residential exposure to ambient air pollution and the development of PD in The Netherlands. Highlights: The role of air pollution in Parkinson's disease (PD) is poorly understood. We examined 16 years of air pollution and PD in a case-control study of 1290 people. No positive relationship between air pollution in the 16 years and PD was observed.